Strategic Design of Policy Establishment on the Cloud Service - Choong Hyong LEE, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Cloud is defined as an information processing system that enables flexible utilization of information and communications resources such as information and communications devices, and software integrated and shared through information and communications networks in response to changes in User Speed data. Especially in today's data-intensive environments, enterprises need to efficiently deploy, store, and process Bigdata. This study identifies how cloud service policies are developed from a national and international perspective, identifies trends, and establishes strategies for strategic implementation before introducing private clouds. To this end, I will first segment the research on basic guidelines into domestic and international policies, analyze cloud policies, and analyze how they will be considered when introducing the cloud. This will determine the direction of application of cloud services through cloud legislation and system analysis. I also plan to determine enterprises' cloud goals and establish comprehensive policies for the cloud services.